Pendekatan Komunikasi Pemasaran Digital oleh Komunitas Fandom SBT Enhypen di Platform X - Widyaswari, Ni Kadek Wulan; Anggreswari, Ni Putu Yunita; Pratiwi, Nuning Indah; Ramadiansyah, Sahri Aflah (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to analyze the digital marketing communication strategies of the SBT Enhypen fandom community in promoting K-Pop merchandise through the X platform (formerly Twitter). As part of the global K-Pop culture, fandoms have become active agents of digital marketing, transforming fan participation into a form of collective consumption and brand advocacy. Using a theoretical study approach, this research explores how communication strategies on social media—particularly on X—serve to build awareness, engagement, and loyalty among fans. The analysis draws upon concepts of digital marketing communication, the promotion mix, and the AIDA model. The findings reveal that fandom-based digital marketing employs a combination of interactive communication, emotional attachment, and cultural identity narratives to drive consumption behavior. Moreover, the SBT Enhypen community illustrates how user-generated content, hashtags, and real-time interactions can function as powerful tools for product dissemination and fan mobilization. In conclusion, digital marketing communication within fandoms not only contributes to product promotion but also reinforces the cultural ecosystem of participatory media in contemporary pop culture.